Competition in a Market for Informed Experts' Services - Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Many important services share the feature that the seller is also the expert who determines who much of the service is needed. Even when the outcomes of such service are observable, it might be difficult for the customer to determine what the expert actually did and whether it was needed. This paper presents a simple model of a market of this type and investigates how the information asymmetries characteristic of such markets might affect their organization. The main insights of this paper are as follows. The asymmetry of information special to these markets may induce vertical specialization. When experts are liable to make diagnosis errors, there is a negative search externality present in such markets which tends to raise prices. The search-cum-diagnosis costs and the accuracy of diagnoses play a clear role in the determination of the market's form of organization: when the former are low and the latter is high, the market is more likely to be organized in a way whereby experts provide binding estimates in advance and consumers search; otherwise the more likely organization is that customers are billed after the service was performed and experts are disciplined by reputation.
Keywords: 330